How do individuals repay their debt?: the balance-matching heuristic - Gathergood, John; Mahoney, Neale; Stewart, Neil; Weber, Jörg (American Economic Association, 2018)
We study how individuals repay their debt using linked data on multiple credit cards. Repayments are not allocated to the higher interest rate card, which would minimize the cost of borrowing. Moreover, the degree of misallocation is invariant to the economic stakes, which is inconsistent with optimization frictions. Instead, we show that repayments are consistent with a balance-matching heuristic under which the share of repayments on each card is matched to the share of balances on each card. Balance matching captures more than half of the predictable variation in repayments and is highly persistent within individuals over time.